Phosphorylation activates the insulin receptor tyrosine protein kinase. - Rosen, O M (1983)
Preparations of insulin receptor from cultured 3T3-L1 adipocytes and human placenta previously was found to catalyze the phosphorylation of the 90,000-dalton component of the insulin receptor on tyrosine residues. This insulin-dependent phosphorylation has now been shown to coincide with the generation of an activated, insulin-independent, receptor protein kinase. Activation is dependent upon ATP, divalent cations (Mg2+ and Mn2+), and insulin (half-maximal activation occurs at 6-8 nM insulin). The time required for activation is consistent with that needed for insulin-dependent self-phosphorylation of the receptor present in eluates from wheat germ lectin-agarose columns and in preparations of affinity-purified placental receptor. Activation proceeds unabated in the presence of soybean trypsin inhibitor at 0.1 mg/ml and the activated, insulin-independent, protein kinase sediments in 5-20% sucrose gradients at the same position as the unmodified receptor. Under steady-state conditions, the phosphorylated receptor binds insulin in the same fashion as the unmodified receptor. It is proposed that the self-phosphorylated form of the receptor is the insulin-activated protein kinase that catalyzes the phosphorylation of exogenous protein and peptide substrates. A corollary of this hypothesis is that enzymatic dephosphorylation may be essential for reversibly terminating the activity of the insulin-receptor protein kinase.